Professional Scala - Janek Bogucki, Alessandro Lacava, Aliaksandr Bedrytski, Matthew de Detrich, Benjamin Neil (Wiley, 2016)
Professional Scala provides experienced programmers with fast track coverage aimed at supporting the use of Scala in professional production applications. Skipping over the basics and fundamentals of programming, the discussion launches directly into practical Scala topics with the most up-to-date coverage of the rapidly-expanding language and related tools. Scala bridges the gap between functional and object-oriented programming, and this book details that link with clear a discussion on both Java compatibility and the read-eval-print loop used in functional programming. You'll learn the details of tooling for build and static analysis. You'll cover unit testing with ScalaTest, documentation with Scaladoc, how to handle concurrency, and much more as you build the in-demand skill set required to use Scala in a real-world production environment. Java-compliant with functional programming properties, Scala's popularity is growing quickly—especially in the rapidly expanding areas of big data and cluster computing. This book explains everything professional programmers need to start using Scala and its main tools quickly and effectively. Master Scala syntax, the SBT interactive build tool, and the REPL workflow * Explore functional design patterns, concurrency, and testing * Work effectively with Maven, Scaladoc, Scala.js, and more * Dive into the advanced type system * Find out about Scala.js A working knowledge of Scala puts you in demand. As both the language and applications expand, so do the opportunities for experienced Scala programmers—and many positions are going unfilled. Twitter, Comcast, Netflix, and other major enterprises across industries are using Scala every day, in a number of different applications and capacities. Professional Scala helps you update your skills quickly to start advancing your career.